Analysis of the Implementation of Productive Sharia Fintech Financing for MSMEs in Increasing the Economic Independence of Communities in Indonesia - Farhan Syafiq; Tri Inda Fadhila Rahma; Muhammad Syahbudi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting Indonesia's economic growth through job creation, increased community income, and strengthening the local economy. However, limited access to capital, low financial literacy, and business management constraints remain obstacles for some MSMEs in developing their businesses. This study aims to analyze the implementation of productive Islamic financing in supporting MSME development and encouraging increased economic independence for communities in Indonesia using a Systematic Literature Review (SLR) approach. Data were obtained from various scientific literature in the form of relevant national and international journals, then analyzed using qualitative descriptive methods to identify patterns, relationships, and previous research findings related to Islamic financing and MSMEs. The study results indicate that Islamic financing has a positive contribution in helping MSMEs gain access to capital through mechanisms based on the principles of fairness, cooperation, and risk sharing. This financing not only helps increase production capacity and business development but also plays a role in creating sustainable economic independence for communities. Furthermore, the development of financial technology such as Islamic fintech presents new opportunities to expand access to financing for MSMEs. However, the implementation of Islamic financing still faces several challenges, such as low Islamic financial literacy, limited access to formal financial services, and suboptimal business fund management. Therefore, increased financial education, business mentoring, the use of digital technology, and collaboration between the government, Islamic financial institutions, and MSMEs are needed to ensure that Islamic financing can become a more effective, inclusive, and sustainable economic empowerment instrument in Indonesia.